(untitled) (Sociología y tecnociencia, 2020)
Argumentation is the way in which reasoning is proposed with the intention of supporting an idea. Social media as means of digital participation give rise to numerous debates in multiple fields and areas of social incidence. The problem is knowing if any type of participation in these platforms are really valid forms of argumentation. This work shows how to recognize formal arguments (at the structure level) within digital discussions and in contrast, inconsequential comments that do not comply with the form of an argument itself. Given the supposed idea that images do not make arguments, here it is shown how they manage to transmit information that can be considered a type of non-verbal argumentation, taking into account the paper of Marraud (2019).